Medicinal importance of Cassia alata L. (Fabaceae): A comprehensive review - Turista, Dora Dayu Rahma; Lathifah, Qurrotu A’yunin; Puspitasari, Eka; Murtadlo, Ahmad Affan Ali; Aini, Nur Sofiatul (Generasi Biologi Indonesia, 2024)
Cassia alata included in the Fabaceae family which spread in tropical and humid areas. All part of the C. alata contains phytochemical so that C. alata is potential medicinal plants. Leaves extract was reported to produce flavonoids, alkaloid, tannin, and cynogenic glycoside. Stems extract contains alkaloid, flavonoid, saponins, oxalate, pheno, and tannin. Roots extract contains alkaloid, saponins, flavonoids, tannins, and phenols. Flower contains saponin, tannin, anthraquinones, flavonoid, glicoside, steroid, and volatile oil. C. alata has been reported to be antiinflamatory, antioxidant, antibacterial, antifungal, antiviral, antiparasitic, antitumor, anticancer, antidiabetic, hepatoprotective, and have a laxative effect. The aim of this study is to give a sneak peek view on C. alata’s taxonomy, distribution, phytochemical, pharmacological activities, and the toxicological effects.